1992
DOI: 10.1101/gad.6.5.837
|View full text |Cite
|
Sign up to set email alerts
|

SR proteins: a conserved family of pre-mRNA splicing factors.

Abstract: We demonstrate that four different proteins from calf thymus are able to restore splicing in the same splicing-deficient extract using several different pre-mRNA substrates. These proteins are members of a conserved family of proteins recognized by a monoclonal antibody that binds to active sites of RNA polymerase II transcription. We purified this family of nuclear phosphoproteins to apparent homogeneity by two salt precipitations. The family, called SR proteins for their serine-and arginine-rich carboxy-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
767
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(788 citation statements)
references
References 47 publications
(66 reference statements)
18
767
0
3
Order By: Relevance
“…These proteins likely arise from the same gene, because most of the ORFs are identical. Individual SR proteins contain one or two amino-terminal RNP-type RNA-binding domains (RBD), and form part of a superfamily of proteins characterized by domains rich in serine/arginine dipeptide repeats, the so-called SR domains (Zahler et al 1992). The RBD consists of RNP-2 and the highly conserved RNP-1, which contains the signature sequence RDAEDA and is important for RNA interaction in a substrate-dependent manner (Reed 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins likely arise from the same gene, because most of the ORFs are identical. Individual SR proteins contain one or two amino-terminal RNP-type RNA-binding domains (RBD), and form part of a superfamily of proteins characterized by domains rich in serine/arginine dipeptide repeats, the so-called SR domains (Zahler et al 1992). The RBD consists of RNP-2 and the highly conserved RNP-1, which contains the signature sequence RDAEDA and is important for RNA interaction in a substrate-dependent manner (Reed 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The arginine-serine-rich (SR) proteins ( Figure 1a) constitute a family of essential splicing factors (Krainer et al, 1990a;Ge et al, 1991;Zahler et al, 1992) that recognize both splice sites and exonic splicing enhancers, and in¯uence alternative processing decisions when their relative concentrations are altered in vivo or in vitro (Ge and Manley, 1990;Krainer et al, 1990b;Zahler et al, 1993a;Ca ceres et al, 1994;Wang and Manley, 1995). SR proteins have been observed to in¯uence splicing activity via their binding to both splice sites and special splicing accessory sequences known as enhancers (Zahler et al, 1993b;Fu, 1995;Manley and Tacke, 1996;Valcarcel and Green, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated substrate-speci®c binding and activity for individual SR proteins (Fu, 1993;Sun et al, 1993;Zahler et al, 1993a;Ca ceres et al, 1994;Wang and Manley, 1995;Chandler et al, 1997;Liu et al, 1998). Furthermore, individual SR proteins have distinct tissue distributions (Zahler et al, 1992;Screaton et al, 1995;Ca ceres and Krainer, 1997). These observations have led to suggestions that alterations in the levels of SR proteins could be determinative for alternative splicing during development.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions are carried out by a large catalytic complex, the spliceosome. Assembly of the spliceosome involves a set of particules or small nuclear ribonucleoproteins (snRNPs) (Guthrie and Patterson, 1988) and numerous splicing factors such as the SR proteins (Zahler et al, 1992) which are thought to help recruit the U1 snRNP to the 5' splice site of the pre-mRNA (Jamison et al, 1995). The U1 snRNP binds at the 5' splice site via RNA : RNA base-pairing.…”
Section: Discussionmentioning
confidence: 99%